Does CEO power matter for the performance of retrenchment strategy? - Brahmana, Rayenda Khresna; You, Hui Wei; Kontesa, Maria (Emerald Publishing Limited, 2020)
Purpose – This research aims to examine the moderating role of CEO power on the relationship between retrenchment strategy and firm performance by framing the relationship under an agency theory, and power circulation theory.